A cohesive-frictional force field (CFFF) for colloidal calcium-silicate-hydrates. (December 2017) - Palkovic, Steven D.; Yip, Sidney; Büyüköztürk, Oral
Abstract: Calcium-silicate-hydrate (C-S-H) gel is a cohesive-frictional material that exhibits strength asymmetry in compression and tension and normal-stress dependency of the maximum shear strength. Experiments suggest the basic structural component of C-S-H is a colloidal particle with an internal layered structure. These colloids form heterogeneous assemblies with a complex pore network at the mesoscale. We propose a cohesive-frictional force field (CFFF) to describe the interactions in colloidal C-S-H materials that incorporates the strength anisotropy fundamental to the C-S-H molecular structure that has been omitted from recent mesoscale models. We parameterize the CFFF from reactive force field simulations of an internal interface that controls mechanical performance, describing the behavior of thousands of atoms through a single effective pair interaction. We apply the CFFF to study the mesoscale elastic and Mohr–Coulomb strength properties of C-S-H with varying polydispersity and packing density. Our results show that the consideration of cohesive-frictional interactions lead to an increase in stiffness, shear strength, and normal-stress dependency, while also changing the nature of local deformation processes. The CFFF and our coarse-graining approach provide an essential connection between nanoscale molecular interactions and macroscale continuum behavior for hydrated cementitious materials.